1998
DOI: 10.1097/00007632-199804150-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Surface Measurement of Head and Neck Posture and the Anatomic Position of the Upper Cervical Vertebrae

Abstract: Anatomic alignment of the upper cervical vertebrae cannot be inferred from variation in surface measurement of head and neck posture. This is the case even in those people identified with more extreme head and neck postural tendencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 17 publications
1
62
0
4
Order By: Relevance
“…Factors affecting reliability of postural measures need to be identified. These may be related to 1) the person's physiological factors such as balance or sway problem during stance; 2) measurement technique (misplacement of the tool) and ability to identify the bony landmarks, 3) the device itself and 4) the number of investigators [44,80,81]. According to Mayer et al [81] the most important factor affecting reliability is the test administrator training followed by the human/device interface error, the magnitude of the movement evaluated, the device error and human performance variability (balance problem, age, gender, motivation).…”
Section: Direct Body Measurements By Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors affecting reliability of postural measures need to be identified. These may be related to 1) the person's physiological factors such as balance or sway problem during stance; 2) measurement technique (misplacement of the tool) and ability to identify the bony landmarks, 3) the device itself and 4) the number of investigators [44,80,81]. According to Mayer et al [81] the most important factor affecting reliability is the test administrator training followed by the human/device interface error, the magnitude of the movement evaluated, the device error and human performance variability (balance problem, age, gender, motivation).…”
Section: Direct Body Measurements By Other Methodsmentioning
confidence: 99%
“…Only few authors have reported the concurrent validity of posture indices measured from photographs and it was with X-rays [31, 39,44,45] (Table 1) …”
Section: Body Angle or Distance Calculation From Photographsmentioning
confidence: 99%
“…In viewing the patient from the side, there was evidence of a significant amount of thoracic humping and concomitant rounded shoulders. However, because visual posture examination is not reliable for determining the sagittal spinal curves (9), it was necessary to conduct a radiological examination to determine the patient's cervical and lumbar curve measurements, and compare these values to normal ranges (10). Thoracic films were not ordered since there was nothing in either the history or physical exam that warranted these films according to current radiographic guidelines (11).…”
Section: Case Reportmentioning
confidence: 99%
“…However, the correlations between surface measurements of FHP and radiological findings of FHP have been shown to be inaccurate. (9,10) A radiographic study was ordered based upon the postural exam findings, and a 2-view series was taken. The series included anteroposterior and lateral cervical views.…”
Section: Case Rep0rtmentioning
confidence: 99%